FAKTOR-FAKTOR YANG MEMENGARUHI FIRM PERFORMANCE DENGAN MODERASI WORKING CAPITAL REQUIREMENT - Salim, Licia Priscilia; Viriany, Viriany (Jurnal Paradigma Akuntansi, 2025)
The purpose of this research is to obtain empirical evidence about the effect of leverage and sales growth with working capital requirements as a moderating variable in food and beverage sub-sector companies listed on the Indonesian Stock Exchange during the period of 2019-2021. This research used 48 samples of financial data in company annual reports that have been selected through a purposive sampling method. Data processing in this research was done using moderation regression analysis helped by the EViews 12 program. The results of this research indicate that leverage has a significant and negative effect on firm performance. The implication of this research is that companies need to continue to improve their company's performance and maintain good financial conditions in order to remain competitive in this world economy.